2010
DOI: 10.1111/j.1468-0084.2009.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced Civic Pride and Integration

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 33 publications
1
34
1
Order By: Relevance
“…Our study contributes to a recently established strand of mostly empirical literature (Alesina and Fuchs-Schündeln 2007, Brosig-Koch et al 2011, Buch and Toubal 2009, Burchardi and Hassan 2011, Burda 2006, Fuchs-Schündeln and Izem 2012, Redding and Sturm 2008, Süssmuth et al 2010, Uhlig 2006 2 that addresses the long-lasting e¤ects of Communism on economically relevant notions twenty years after the collapse of the Soviet system. More than two decades after the fall of the wall it is now possible to study economic behavior of individuals who spent most of their childhood in uni…ed Germany.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our study contributes to a recently established strand of mostly empirical literature (Alesina and Fuchs-Schündeln 2007, Brosig-Koch et al 2011, Buch and Toubal 2009, Burchardi and Hassan 2011, Burda 2006, Fuchs-Schündeln and Izem 2012, Redding and Sturm 2008, Süssmuth et al 2010, Uhlig 2006 2 that addresses the long-lasting e¤ects of Communism on economically relevant notions twenty years after the collapse of the Soviet system. More than two decades after the fall of the wall it is now possible to study economic behavior of individuals who spent most of their childhood in uni…ed Germany.…”
Section: Introductionmentioning
confidence: 98%
“…This is shown in Figure 1. Whether the transition to the new steady state is smooth or perturbed, as suggested, for example, in Süssmuth et al (2010), is unclear as indicated by the dashed hand, West Germans are themselves separately matched to each other. After uni…cation, the two separate Hotelling's circles merge into one and individuals -independently of being of East or West background-get randomly matched.…”
Section: Theoretical Model Of Trust and Cooperationmentioning
confidence: 99%
“…For example, it was reported that sporting success can create a general feel-good factor among the population (see Forrest/Simmons 2003) as well as feelings of national and civic pride (see Allison/Monnington 2002). Moreover, it has a unifying component because it can foster local and national unity and social cohesion (see Castellanos et al 2011;Johnson 2008;Süssmuth et al 2010). Previous research has shown that sporting success can contribute to individual happiness and that people find it important for the reputation of their country (see Wicker/Hallmann/Breuer/Feiler 2012).…”
Section: Consumer's Utility and Willingness-to-paymentioning
confidence: 99%
“…For example, hosting such events, or success in them, appears to influence optimism in stock markets [2,17,28,30,42] and subjective well-being [29,40].…”
Section: Introductionmentioning
confidence: 99%